Lipoprotein Fractions and Antithrombin III Consumption During Clotting - Winter, J H; Bennett, B; McTaggart, F; Douglas, A S (Thrombosis and Haemostasis, 1982)
Plasma and serum antithrombin levels were measured in functional (initial rate measurement) and immunological assays together with serum lipid levels in normal subjects and patients with coronary artery disease. Specific antithrombin activity in plasma showed a negative correlation with triglyceride levels. The consumption of antithrombin activity during blood clotting was negatively correlated with both serum total triglyceride and heparin precipitable lipoprotein and positively correlated with serum high density lipoprotein cholesterol. Different blood lipoprotein fractions may influence the activity of the antithrombin III molecule.
Keywords: Keywords Antithrombin III; Lipoproteins